Pengaruh Kualitas Produk, Harga dan Distribusi terhadap Volume Penjualan ARB Bakery di Kelurahan Sukmajaya - Toto Widiarto; Ema Hardiana (Universitas Indraprasta PGRI, 2021)
ARB (Original New Flavor) Bakery is a fast-growing business in the food industry sector, especially snacks made from wheat flour. Where this business must always be able to keep up with the changes that occur along with the development of an increasingly advanced business world. Including finding new techniques, as well as ways to be able to increase the sales volume which is the company’s goal. However, on the one hand, the company has not been too focused on the development of marketing such as market research, especially research related to the sale of ARB bread. The purpose of this research is to determine whether product quality, price, and distribution significantly influence the sales volume of ARB (Original New Flavor) Bakery in Sukmajaya urban village. This research was conducted by giving questionnaires to 20 respondents. The research method uses multiple linear regression analysis to determine the effect of independent variables (X) in this case is product quality, price and distribution to the dependent variable (Y) in this case is sales volume with the the help of SPSS version 27.00 software. Based on the results and discussion it can be concluded that simultaneously quality of product, price, and distribution have a positive and significant effect on the sales volume of ARB (Original New Flavor) Bakery in Sukmajaya urban village, it is obtained by the results of testing the the hypothesis that shows the value of f count>f table (10,175>3,246). And the test results partially state that the variables of product quality, price, and distributionhave a positive and significant effect on the sales volume of ARB (Original New Flavor) Bakery in Sukmajaya urban village with a value of t count>t table (2,575>2,120). This is evidenced by the results of the f hypothesis test simultaneously and partially of t hypothesis test in data analysis.